Code-switching and multilingualism in literature. (August 2015) - Gardner-Chloros, Penelope; Weston, Daniel
Code-switching in spoken modes has now been studied fairly extensively and is better understood at the conversational as well as the grammatical level. However, interest in written code-switching has developed more slowly and is still represented mainly in relation to specific periods, such as the Classical period and the medieval period, where a large number of works have now appeared. Linguists have questioned to what extent the models developed for spoken code-switching can be applied to writing, and a fortiori to literary writing. This introductory article reviews the main types of literary multilingualism and the main functions of code-switching within it. We conclude that there is at least a partial – and not inconsiderable – overlap between the functions of code-switching in spoken and written modalities.